Integration of Pancasila Values and Islamic Teachings in Civic Education from the Perspective of the Qur’an and Hadith and Its Implications for Educational Participation and Gender Equality in Bangka Regency - Pradipta, Frans Tory Damara; Saputra, Aldian Kurniawan (The Future of Education Journal, 2026)
This study examines the integration of Pancasila values and Islamic teachings in civic education from the perspective of the Qur’an and Hadith, and its implications for educational participation and gender equality in Bangka Regency. The study is motivated by the need to strengthen civic education through a value-based approach that aligns national ideology with religious principles. This research employs a qualitative approach using library research methods, drawing on scholarly journal articles and normative sources, including the Qur’an and Hadith. Data were analyzed using content analysis to identify conceptual relationships and thematic patterns. The findings indicate that Pancasila values, such as divinity, humanity, and social justice, are substantively aligned with Islamic teachings, particularly in promoting equality, justice, and moral responsibility. The Qur’anic perspective emphasizes the equality of all human beings regardless of gender, supporting equal access to education as a fundamental right. The integration of these values in civic education contributes to strengthening moral awareness and encouraging active participation in education. However, the study also identifies challenges in implementation, including socio-cultural barriers and limited contextual understanding of religious teachings, which may hinder gender equality in educational access and participation. The study concludes that a more systematic and contextualized approach is needed to effectively integrate these values in civic education. Further empirical research is recommended to explore practical implementation and its impact at the local level.